1 Records of the Governor and Company of the Massachusetts Bay 190 (1853) - (:unkn) unknown (My University, 1636)
"Whearas many complaints have bene made to this Court, both formerly & at psent, of the great neglect of all sorts of people of vseing the lawfull & necessary meanes of their safety, especially in this time of so much danger great fro the Indians, it is therefore ordered, that the millitary officers in every towne shall pride that the watches bee dewely kept in places most fit for danger by In- common safetie, & also a ward on the Lords dayes, the same to begin before the end of this first month, & to bee continued vntill the end of September ; & that every pson above the age of 18 yeares (except magistrats & elders of the churches) shalbee compellable to this servise, either in pson or by some substitute, to bee alowed by him that hath the charge of the watch or warde for that time, vpon paine of 5s for every default, to bee levyed by distresse by the surveyar of the armes, & to bee implyed for light & fyer, & such necessaries, by the discretion of the millitary officers./"
Keywords: REQUIRED POSSESSION